HER2 positive metastatic breast cancer: What happens after first line failure? - Chan, Arlene (Cancer Council Australia, 2016)
For women with metastatic HER2 positive breast cancer, the introduction of trastuzumab into routine practice was transformative. More recently, the addition of pertuzumab has further improved the outlook. However in almost all cases, the disease unfortunately progresses. Much research has gone into what to do next. Fortunately we now have evidence to support a number of strategies, with the underlying understanding that HER2 blockade should be continued for as long as possible. Historically, lapatinib was the first anti-HER2 agent to show activity after relapse on trastuzumab. Subsequently the effectiveness of T-DM1 (Kadcyla) has been demonstrated, as has the use of alternating chemotherapy agents with trastuzumab. Research is now focussed on understanding and combating the mechanisms of resistance to anti-HER2 agents that inevitably develop. Promising data suggest that mTOR inhibitors, PI3 kinase inhibitors and immune-Activating therapies may be helpful.